Merger Dalam Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas dan Kegiatan Yang Dilarang Menurut Undang-Undang Nomor 5 Tahun 1999 Tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat - Jenny Kristina Matuankotta (Faculty of Law, Universitas Pattimura, 2012)
Merger as a merger of companies regulated in Act Number 40 of 2007. The arrangement of the merger is also regulated in Act Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. Merger is closely associated with the potential for monopolistic practices and or unfair business competition, because it's basically the essence of the merger is the added value of the companies that are merging. Actions such merger should be prohibited and regulated in the law because it can cause negative effects to healthy market competition. Many people who suffer losses potentially caused by the merger, such as minority shareholders, employees, creditors, and other community stakeholders. Setting merger in the legislation is a form of prevention and mitigation activities or mergers that could reduce competition.